Moderating effect of comorbid anxiety disorders on treatment outcome in a randomized controlled psychotherapy trial in early‐onset persistently depressed outpatients. Issue 10 (10th September 2018) - Assmann, Nele; Schramm, Elisabeth; Kriston, Levente; Hautzinger, Martin; Härter, Martin; Schweiger, Ulrich; Klein, Jan Philipp
Abstract : Background: Persistent depressive disorder (PDD) is associated with high rates of comorbid psychiatric disorders, mostly anxiety disorders (ADs). Comorbid AD was found to be associated with poorer treatment outcome in PDD patients. The effect of comorbid AD on disorder‐specific treatment for PDD (Cognitive Behavioral Analysis System of Psychotherapy [CBASP]) has not been studied yet. Methods: We analyzed whether the presence of a comorbid AD was moderating the effectiveness of disorder‐specific (CBASP) versus nonspecific psychotherapy (supportive therapy [SP]) on depressive symptoms (24‐item Hamilton Rating Scale for Depression [HRSD‐24]) in a sample of unmedicated early‐onset PDD outpatients ( N = 268). Secondary outcomes were response and remission of depressive symptoms and the extent of interpersonal problems (Inventory of Interpersonal Problems [IIP‐64]). Results: The superiority of CBASP over SP was significantly stronger in PDD patients with comorbid AD compared to patients without AD (in HRSD‐24 and IIP‐64). There was no significant moderation for remission or response of depressive symptoms. Discussion: Our hypothesis of a moderating effect of comorbid AD was confirmed. The main limitation might be the exclusion criteria of our sample limiting the generalizability. The major strength is the systematic analysis of the effect of AD in treating early‐onset PDD with high quality of psychotherapy in both arms of this trial. Conclusion: Patients suffering from PDD comorbid with AD might experience greater benefit when they are treated with specific as opposed to unspecific therapy. Analyzing subgroups of patients with PDD seems worthwhile to improve treatment effectiveness even within disorder‐specific treatment programms.